Impermeable concrete composition
By using polycarboxylic acid high-efficiency water reducing agent and active siliceous self-repair waterproofing agent in concrete, combining fly ash and ore powder, adjusting the component ratio, the problem of poor seepage resistance of concrete is solved and efficient seepage resistance is achieved Effect, suitable for construction projects.
Patent Information
- Application Number
- CN202411415697.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
Existing concrete often has water leakage and crack problems during construction, resulting in poor permeability of the building and difficult to meet the high compressive strength, durability and permeability of the building requirements.
Using polycarboxylic acid high-efficiency water reducing agent and active siliceous self-repair waterproofing agent as admixture, combined with fly ash and ore powder as mixed materials, adjust the weight ratio and water-adhesive ratio of each component of the concrete to prepare a kind of anti-seepage resistance The concrete composition improves its impermeability resistance.
It significantly improves the seepage resistance of concrete, reduces water leakage in buildings, and has a simple preparation method, no need to change traditional processes, reduces costs, and is suitable for large-scale construction projects.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and more particularly to an impermeable concrete composition. Background Art
[0002] In the civil engineering construction industry, concrete is an irreplaceable building material. Concrete has the characteristics of abundant raw materials, low price and simple production process, so its usage is increasing. The compressive strength, durability, strength grade and impermeability of concrete are all its more important parameters. According to different construction needs, the civil engineering construction industry is also constantly pursuing concrete with higher compressive strength, better durability and stronger impermeability. Therefore, more and more types of concrete have appeared on the market.
[0003] Leakage and cracks are common defects in construction. Where there is water, there must be a source; where there is leakage, there must be cracks; where there is crack, there must be restraining force. Theoretically, all cracks are the result of force. There are relatively common cracks in concrete structures, and the causes can be divided into two categories: cracks caused by external loads and deformation. Generally speaking, cracks visible to the naked eye can be divided into three types according to their causes:
[0004] 1. Cracks caused by external loads (such as static and dynamic loads), cracks caused by the main stress calculated according to conventional methods;
[0005] 2. Cracks caused by structural secondary stress, that is, cracks caused by discrepancies between the actual working state of the structure and the conventional calculation assumptions;
[0006] 3. Cracks caused by deformation changes, that is, cracks caused by temperature, shrinkage and expansion, uneven settlement and other factors.
[0007] The above-mentioned cracks ultimately lead to water leakage in the building. In order to avoid this phenomenon, an impermeable concrete composition has been developed to reduce the occurrence of water leakage in the building. Summary of the invention
[0008] The purpose of the present invention is to provide an impermeable concrete composition, which has a simple preparation method and strong impermeability.
[0009] The above technical purpose of the present invention is achieved through the following technical scheme: an impermeable concrete composition, the concrete composition includes cement, sand, stone, water, admixtures and mixed materials, the mixed materials are fly ash and mineral powder, and the admixtures are polycarboxylic acid high-efficiency water reducing agent and active silica self-repairing waterproofing agent.
[0010] The present invention is further configured as follows: the weight ratio of the polycarboxylic acid high-efficiency water reducing agent to the active silica self-repairing waterproofing agent is:
[0011] Polycarboxylic acid high-efficiency water reducing agent: active silica self-repairing waterproofing agent = 1.8:1.0.
[0012] The present invention is further configured as follows: the weight ratio of each component in the concrete composition is:
[0013] Cement: sand: stone: water: admixture: mixed materials = 0.9-1.1: 1.65-1.95: 2.35-2.75: 0.35-0.40: 0.035-0.041: 0.33-0.36.
[0014] The present invention is further configured as follows: the weight ratio of each component in the concrete composition is preferably:
[0015] Cement: sand: stone: water: admixture: mixed materials = 1:1.80:2.55:0.38:0.038:0.35.
[0016] The present invention is further configured as follows: the weight ratio of each component in the concrete composition is preferably:
[0017] Cement: sand: stone: water: admixture: mixed materials = 1:1.80:2.55:0.38:0.038:0.35.
[0018] The present invention is further configured as follows: the water-cement ratio of the concrete composition is 0.26-0.30.
[0019] The present invention is further configured as follows: the optimum value of the water-cement ratio of the concrete composition is 0.28.
[0020] The present invention is further configured as follows: the weight ratio of the fly ash to the mineral powder is 2:5.
[0021] The present invention is further configured as follows: the cement strength grade is 42.5R.
[0022] The present invention is further configured as follows: the fineness modulus of the sand is 2.8.
[0023] The present invention is further configured as follows: the stone is 5-10 mm granite crushed stone.
[0024] In summary, the present invention has the following beneficial effects: Most of the existing buildings made of concrete have a separate waterproof layer to achieve a better waterproof effect, and the concrete used in them has poor anti-seepage performance itself.
[0025] In the present invention, the admixture is adjusted to a mixture of a polycarboxylic acid high-efficiency water-reducing agent and an active siliceous self-repairing waterproofing agent, and the parameters for preparing each component of the concrete are further adjusted, thereby achieving a significant improvement in the anti-seepage performance of the concrete composition.
[0026] Its preparation method is no different from that of ordinary concrete, and workers do not need to relearn. The amount of active silica self-repairing waterproofing agent added is not large, and it will not increase or decrease the manufacturing cost of concrete. It can be used in large quantities in construction projects. DETAILED DESCRIPTION
[0027] The present invention is described in further detail below.
[0028] Example 1: An impermeable concrete composition, comprising cement, sand, stone, water, admixture and mixed materials, wherein the cement type is P·0, the strength grade is 42.5R, the mixed materials are fly ash and mineral powder, the weight ratio of fly ash to mineral powder is 2:5. The fineness modulus of the sand is 2.8, and the bulk density is 1480kg / m 3 The stone refers to granite with a size of 5-10 mm, a needle-like particle content of 4%, and an apparent density of 2640 kg / m 3 , bulk density is 1540kg / m 3 , the mud content is 0.4%. The admixtures are polycarboxylic acid high-efficiency water reducing agent and active silica self-repairing waterproofing agent.
[0029] The weight ratio of polycarboxylic acid high-efficiency water-reducing agent and active silica self-repairing waterproofing agent is: polycarboxylic acid high-efficiency water-reducing agent: active silica self-repairing waterproofing agent = 1.8:1.0.
[0030] The water-cement ratio of the concrete composition is 0.26-0.30, and the weight ratio of each component is: cement: sand: stone: water: admixture: mixed material = 0.9-1.1: 1.65-1.95: 2.35-2.75: 0.35-0.40: 0.035-0.041: 0.33-0.36.
[0031] The production process of the above concrete mainly includes raw material preparation, mixing, pouring and curing.
[0032] (1) Raw material preparation: according to the demand, weigh according to the ratio of cement: sand: stone: water: admixture: mixed material = 0.9-1.1: 1.65-1.95: 2.35-2.75: 0.35-0.40: 0.035-0.041: 0.33-0.36.
[0033] (2) Mixing: Mixing is the process of fully mixing the raw materials. Through mixing, the various raw materials can be evenly distributed, thus ensuring the stability of the concrete performance. Mixing equipment usually uses a concrete mixer truck or a concrete mixing station. The mixing time is generally controlled at 3-5 minutes to ensure that the concrete is mixed evenly.
[0034] (3) Pouring: Pouring is the process of pouring concrete into prefabricated formwork or on-site formwork. During the pouring process, the continuity of the concrete needs to be ensured to avoid problems such as cold joints and slag inclusions. At the same time, vibration and compaction are also required according to design requirements to ensure that the concrete is tightly combined and forms a uniform dense body.
[0035] (4) Maintenance: After concrete is poured, proper maintenance is required to ensure its strength and durability. Maintenance generally includes timely covering to keep moisture, proper watering, and controlling ambient temperature. The maintenance time is 7-14 days, and the specific time can be adjusted accordingly according to the concrete mix ratio and environmental conditions.
[0036] The concrete prepared by the above steps will be used in the construction of the "Huangpu Red" Lingtou Black Tea Creative Park Tea Rhythm Station, which is located in Guangzhou. According to statistics, from January 1, 2023 to April 22, 2024, Guangzhou had a total of: 157 rainy days, 132 cloudy days, 114 overcast days, 74 sunny days, and 1 day of sand, fog and haze. It can be seen that there are more rainy days in Guangzhou, so it is extremely important to do a good job of waterproofing buildings. The "Huangpu Red" Lingtou Black Tea Creative Park Tea Rhythm Station, which was built with concrete prepared by this scheme, was completed in October 2023, with a total construction area of 300m 2 , there has been no water seepage so far.
[0037] Example 2: An impermeable concrete composition, comprising cement, sand, stone, water, admixture and mixed materials, wherein the cement type is P·0, the strength grade is 42.5R, the mixed materials are fly ash and mineral powder, the weight ratio of fly ash to mineral powder is 2:5. The fineness modulus of the sand is 2.8, and the bulk density is 1480kg / m 3 The stone refers to granite with a size of 5-10 mm, a needle-like particle content of 4%, and an apparent density of 2640 kg / m 3 , bulk density is 1540kg / m 3 , the mud content is 0.4%. The admixtures are polycarboxylic acid high-efficiency water reducing agent and active silica self-repairing waterproofing agent.
[0038] The weight ratio of polycarboxylic acid high-efficiency water-reducing agent and active silica self-repairing waterproofing agent is: polycarboxylic acid high-efficiency water-reducing agent: active silica self-repairing waterproofing agent = 1.8:1.0.
[0039] The water-cement ratio of the concrete composition is 0.28, and the weight ratio of each component is: cement: sand: stone: water: admixture: mixed material = 1: 1.80: 2.55: 0.38: 0.038: 0.35.
[0040] Example 2 is a preferred embodiment of Example 1. When conducting preliminary tests, 6 standard specimens of 28 days old were selected and tested according to the standard test method of GB 50164 "Concrete Quality Control Standard" to test the maximum water pressure they can withstand. According to the maximum water pressure that the concrete specimens can withstand during the impermeability test, it is found that the 6 standard specimens can withstand static water pressures of 0.8MPa, 0.9MPa, 0.9MPa, 0.8MPa, 0.8MPa, and 1.0MPa respectively without water seepage. It can be seen that its impermeability grade can reach P8 or above, which is a concrete composition with excellent impermeability.
[0041] Example 3: An impermeable concrete composition, comprising cement, sand, stone, water, admixture and mixed materials, wherein the cement type is P·0, the strength grade is 42.5R, the mixed materials are fly ash and mineral powder, and the weight ratio of fly ash to mineral powder is 2:5. The fineness modulus of the sand is 2.8, and the bulk density is 1480kg / m 3 The stone refers to granite with a size of 5-10 mm, a needle-like particle content of 4%, and an apparent density of 2640 kg / m 3 , bulk density is 1540kg / m 3 , mud content is 0.4%. The admixture is polycarboxylic acid high-efficiency water reducer.
[0042] The water-cement ratio of the concrete composition is 0.28, and the weight ratio of each component is: cement: sand: stone: water: admixture: mixed material = 1: 1.80: 2.55: 0.38: 0.024: 0.35.
[0043] During the preliminary test, six standard specimens with an age of 28 days were selected and tested according to the standard test method of GB 50164 "Concrete Quality Control Standard" to test the maximum water pressure they can withstand. According to the maximum water pressure that the concrete specimens can withstand during the anti-permeability test, it was found that the six standard specimens can withstand static water pressures of 0.6MPa, 0.6MPa, 0.5MPa, 0.7MPa, 0.5MPa, and 0.6MPa respectively without water seepage.
[0044] Example 4: An impermeable concrete composition, comprising cement, sand, stone, water, admixture and mixed materials, wherein the cement type is P·0, the strength grade is 42.5R, the mixed materials are fly ash and mineral powder, the weight ratio of fly ash to mineral powder is 2:5. The fineness modulus of the sand is 2.8, and the bulk density is 1480kg / m 3 The stone refers to granite with a size of 5-25 mm, a needle-like particle content of 4%, and an apparent density of 2640 kg / m 3 , bulk density is 1540kg / m 3, the mud content is 0.4%. The admixtures are polycarboxylic acid high-efficiency water reducing agent and active silica self-repairing waterproofing agent.
[0045] The weight ratio of polycarboxylic acid high-efficiency water-reducing agent and active silica self-repairing waterproofing agent is: polycarboxylic acid high-efficiency water-reducing agent: active silica self-repairing waterproofing agent = 1.8:1.0.
[0046] The water-cement ratio of the concrete composition is 0.28, and the weight ratio of each component is: cement: sand: stone: water: admixture: mixed material = 1: 1.80: 2.55: 0.38: 0.038: 0.35.
[0047] During the preliminary test, six standard specimens with an age of 28 days were selected and tested according to the standard test method of GB 50164 "Concrete Quality Control Standard" to test the maximum water pressure they can withstand. According to the maximum water pressure that the concrete specimens can withstand during the anti-permeability test, it was found that the six standard specimens can withstand static water pressures of 0.7MPa, 0.5MPa, 0.5MPa, 0.5MPa, 0.6MPa, and 0.5MPa respectively without water seepage.
[0048] Comparative Example 1: A concrete composition, comprising cement, sand, stone, water, admixture and mixed materials, wherein the cement type is P·0, the strength grade is 42.5R, the mixed materials are fly ash and mineral powder, and the weight ratio of fly ash to mineral powder is 15:14. The fineness modulus of sand is 2.7. The stone refers to granite with a specification of 5-25 mm. The admixture is a polycarboxylic acid high-efficiency water reducing agent.
[0049] The water-cement ratio of the concrete composition is 0.44, and the weight ratio of each component is: cement: sand: stone: water: admixture: mixed material = 1: 3.26: 4.65: 0.72: 0.030: 0.63.
[0050] Similarly, six standard specimens of 28 days old were taken and tested according to the standard test method of GB 50164 "Concrete Quality Control Standard" to test the maximum water pressure they can withstand. According to the maximum water pressure that the concrete specimens can withstand during the anti-permeability test, it was found that the six standard specimens can withstand static water pressures of 0.3MPa, 0.4MPa, 0.3MPa, 0.3MPa, 0.3MPa, and 0.3MPa respectively without water seepage.
[0051] Comparative Example 2: A concrete composition, comprising cement, sand, stone, water, admixture and mixed materials, wherein the cement type is P·0, the strength grade is 42.5R, the mixed materials are fly ash and mineral powder, and the weight ratio of fly ash to mineral powder is 51:89. The fineness modulus of sand is 2.9. The stone refers to granite with a specification of 5-25 mm. The admixture is a polycarboxylic acid high-efficiency water reducing agent.
[0052] The water-cement ratio of the concrete composition is 0.44, and the weight ratio of each component is: cement: sand: stone: water: admixture: mixed material = 1: 3.76: 5.19: 0.79: 0.040: 0.68.
[0053] Similarly, six standard specimens of 28 days old were taken and tested according to the standard test method of GB 50164 "Concrete Quality Control Standard" to test the maximum water pressure they can withstand. According to the maximum water pressure that the concrete specimens can withstand during the permeability test, it was found that the six standard specimens can withstand static water pressures of 0.2MPa, 0.3MPa, 0.2MPa, 0.4MPa, 0.3MPa, and 0.3MPa respectively without water seepage.
[0054] Comparative Example 3: A concrete composition, comprising cement, sand, stone, water, admixture and mixed materials, wherein the cement variety is P·11, the strength grade is 42.5R, the mixed materials are fly ash and mineral powder, and the weight ratio of fly ash to mineral powder is 24:17. The fineness modulus of sand is 2.7. The stone refers to granite with a specification of 5-31.5 mm. The admixture is a polycarboxylic acid high-efficiency water reducing agent.
[0055] The water-cement ratio of the concrete composition is 0.47, and the weight ratio of each component is: cement: sand: stone: water: admixture: mixed material = 1: 3.54: 5.10: 0.80: 0.029: 0.70.
[0056] Similarly, six standard specimens of 28 days old were taken and tested according to the standard test method of GB 50164 "Concrete Quality Control Standard" to test the maximum water pressure they can withstand. According to the maximum water pressure that the concrete specimens can withstand during the anti-permeability test, it was found that the six standard specimens can withstand static water pressures of 0.2MPa, 0.4MPa, 0.3MPa, 0.4MPa, 0.4MPa, and 0.4MPa respectively without water seepage.
[0057] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. An impermeable concrete composition, characterized in that: The concrete composition comprises cement, sand, stone, water, admixture and mixed materials, wherein the mixed materials are fly ash and mineral powder, and the admixtures are polycarboxylic acid high-efficiency water reducing agent and active silica self-repairing waterproofing agent.
2. The impermeable concrete composition according to claim 1, characterized in that: The weight ratio of the polycarboxylate high-efficiency water-reducing agent to the active silica self-repairing waterproofing agent is: Polycarboxylic acid high-efficiency water reducing agent: active silica self-repairing waterproofing agent = 1.8:1.
0.
3. The impermeable concrete composition according to claim 1, characterized in that: The weight ratio of each component in the concrete composition is: Cement: sand: stone: water: admixture: mixed materials = 0.9-1.1: 1.65-1.95: 2.35-2.75: 0.35-0.40: 0.035-0.041: 0.33-0.
36.
4. The method for preparing an impermeable concrete composition according to claim 1, characterized in that: The weight ratio of each component in the concrete composition is preferably: Cement: sand: stone: water: admixture: mixed materials = 1:1.80:2.55:0.38:0.038:0.
35.
5. The impermeable concrete composition according to claim 1, characterized in that: The water-cement ratio of the concrete composition is 0.26-0.
30.
6. The impermeable concrete composition according to claim 1, characterized in that: The optimum value of the water-binder ratio of the concrete composition is 0.
28.
7. The impermeable concrete composition according to claim 1, characterized in that: The weight ratio of the fly ash to the mineral powder is 2:
5.
8. The impermeable concrete composition according to claim 1, characterized in that: The cement strength grade is 42.5R.
9. The impermeable concrete composition according to claim 1, characterized in that: The fineness modulus of the sand is 2.
8.
10. The impermeable concrete composition according to claim 1, characterized in that: The stone is 5-10 mm granite crushed stone.